72-hour advertising challenge with generative AI in an undergraduate graphic design module: A case study - Wong, Shaw Chiang; Tan, Huey Wen; Ooi, Kok Hor (Australasian Journal of Educational Technology, 2025)
Interest in using generative artificial intelligence (GenAI) in design education is growing, yet its impact on students’ creative processes and motivation remains underexplored, especially in advertising design. This qualitative exploratory case study examined how GenAI tools influenced 12 undergraduate graphic and multimedia design students during a 72-hour advertising challenge with GenAI at a private Malaysian university. Grounded in sociocultural theory’s zone of proximal development and self-determination theory, the study explored how GenAI functioned as an instructional support. Data were collected through three focus group discussions and analysed thematically. Findings suggest that GenAI enhanced ideation, visualisation and collaboration, supporting students’ sense of competence and relatedness. However, concerns emerged around creative autonomy and dependence on AI. The study positions GenAI as a conditional more knowledgeable other and highlights the importance of pedagogical strategies that foster critical reflection and ethical use. These insights contribute to the emerging discourse on AI in design education by connecting theory with empirical evidence and offering practical implications for curriculum development. Implications for practice or policy: Design educators should integrate GenAI tools thoughtfully to enhance creativity while ensuring students retain critical thinking and originality. Assessments should incorporate reflection to help students critically engage with AI-generated content and develop technical proficiency. Higher educational institutions must update curricula to align with evolving GenAI capabilities and industry needs. Ethical AI use should be emphasised to ensure responsible adoption in education and professional practice.